MN-ANDALUSITE, SPESSARTINE, MN-GROSSULAR, PIEMONTITE AND MN-ZOISITE/CLINOZOISITE FROM TRIKORFO, THASSOS ISLAND, GREECE - Voudouris, P.; Graham, I.; Mavrogonatos, K.; Su, S.; Papavasiliou, K.; Farmaki, M.-V.; Panagiotidis, P. (Bulletin of the Geological Society of Greece, 2016)
Mylonitized manganiferous schists and calc-silicate layers intercalated within amphibolite- to greenschist facies mica schists from the Trikorfo area (Thassos Island, Greece), host an unusual Mn-rich paragenesis of metamorphic silicate minerals, most of them in large, gemmy crystals. The silicates occur both in layers subparallel to the foliation and within discordant veins cross-cutting the metamorphic fabric. Piemontite (up to 12.7 wt. % Mn2O3), Mn-rich epidote (up to 7.8 wt. % Mn2O3), Mn-rich andalusite (up to 15.6 wt. % Mn2O3), Mn-poor pink clinozoisite-epidote (up to 0.87 wt. % Mn2O3), Mn-poor pink zoisite (up to 0.21 wt. % Mn2O3), spessartine (up to 47.7 wt. % MnO) and Mn-rich grossular (up to 3.6 wt. % MnO) are associated with diopside, hornblende, phlogopite, muscovite, tourmaline, hematite and iron-bearing kyanite. The studied assemblages are indicative of high fO2 conditions due to the presence of highly oxidized pre-metamorphic Mn-rich mineral associations. They developed during prograde metamorphism of a Mn-rich sedimentary protolith(s), followed by re equilibration to post-peak metamorphic conditions, vein formation and metasomatism during retrograde metamorphism accompanying the exhumation of the Thassos Island during the Oligocene-Miocene. Alternatively, the skarn similar mineralogy of the calc-silicate layers could have been formed by fluids released by granitoids during contact metamorphism. The studied area represents a unique mineralogical geotope. Its geological-mineralogical heritage should be protected through establishment of a mineralogical-petrological geopark that will also promote sustainable development of the area.